HYPNOTIZABILITY AND PAIN MODULATION: A Body–Mind Perspective. Issue 3 (3rd July 2018) - Varanini, Maurizio; Balocchi, Rita; Carli, Giancarlo; Paoletti, Giulia; Santarcangelo, Enrica L.
Abstract: The study investigated whether the cardiac activity and cognitive–emotional traits sustained by the behavioral inhibition/activation system (BIS/BAS) may contribute to hypnotizability-related pain modulation. Nociceptive stimulation (cold-pressor test) was administered to healthy participants with high (highs) and low (lows) hypnotizability in the presence and absence of suggestions for analgesia. Results showed that heart rate increased abruptly at the beginning of nociceptive stimulation in all participants. Then, only in highs heart rate decreased for the entire duration of hand immersion. During stimulation with suggestions of analgesia, pain threshold negatively correlated with heart rate. BIS/BAS activity partially accounted for the observed hypnotizability-related differences in the relation between cardiac interoception and pain experience.